The Relationship Between The Duration Of Hypertension With The Rate of Depression in Hypertension Patients in Outpatient Care at The Heart and Vascular Polyclinic of The Surabaya Jemursari Islamic Hospital - Thoriqi, Mochammad Hafitd; Ahmad Ali Firdaus, Abraham; Retno Kusumawati, Diah; Masdan Salim, Hotimah (Prominentia Medical Journal, 2024)
Hypertension is one of the risk factors that can increase the occurrence of depression. Generally, people diagnosed with hypertension have a difficult experience and also often experience somatic symptoms that cause a low quality of life for patients. All of these factors can cause people diagnosed with hypertension to tend to be easier to get psychological pressure, especially depression. The Objectivein in this research is to determine the relationship between the duration of hypertension with the rate depression in hypertension patients at the heart and vascular polyclinic of the Surabaya Jemursari Islamic Hospital. This type of research is analytic observational with purposive sampling. Respondents in this study were hypertension patients who were treated at the cardiovascular and vascular disease polyclinic at the Surabaya Jemursari Islamic Hospital, amounting to 67 people. Collecting data using a depression rate questionnaire Patient Health Questionnaire (PHQ-9). The result is known that from 67 respondents it was found that the majority had hypertension for 1-5 years, namely 37 respondents (55.2%), 6-10 years as many as 12 respondents (17.9%) and more than 10 years as many as 18 respondents (26.9 %). And as many as 13 respondents (19.4%) had no symptoms of depression, 50 respondents (74.6%) had mild depressive symptoms, 4 respondents (6%) had mild depression and there were no respondents with moderate or severe depression. After the data was processed using the chi square test with a confidence probability of p value=0.05 to determine the relationship between the two, the p-value was 0.106, because the p-value>0.05. Then the research hypothesis is rejected. The conclusion is there is no relationship between the duration of hypertension with the rate of depression in patients with hypertension at the heart and vascular polyclinic of the Surabaya Jemursari Islamic Hospital